A Review on Design Optimization of Automotive Conventional Differential System for Rear Wheel Drive - Ashwin Naik; Suryakant Kadam; Sachin More; Gopal Kate; Nilesh Raut (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
The following review paper provides a thorough explanation of the limitations of the automotive conventional differential system under various circumstances and suggests a viable solution for each constraint by enhancing the differential unit's design and construction. The conventional differential used in automotive (CAR, TRUCKS etc.) is the system which is used to transmit power from the engine to the rear wheels of the vehicle via the propeller shaft, hence we can say that the differential works on the principle of eliminating the tractional difference between the rear wheels of the vehicle. The main function of the differential system is to distribute equal power to the rear wheel when the vehicle is moving straight and to increase the speed of the outer wheel and decrease the speed of the inner wheel when the vehicle makes a turn (LEFT OR RIGHT) and vice versa, because the radius of turn of the outer wheel is greater than the radius of turn of the inner wheel. The main limitation of the conventional differential is that when the vehicle is stuck in a pit/mud there is loss of traction (in the rear wheels) as the differential unit ceases the power transmitted wheel. This paper describes the characteristics to be optimized of the conventional automotive differential system to improve vehicle stability and provide the necessary traction.
Keywords: Differential; Traction; Turning–Radius; Wheels; torque